Modulation of rat aortic contractions by ultradisperse TiO2 nanoparticles of crystalline forms of anatase and rutile - Platon Zub; Olga Tsymbalyuk; Oleksandr Chunikhin; Tamara Davydovska; Stanislav Myakushko; Khrystyna Sholota; Ivan Voiteshenko; Oleksandr Tsuvariev; Sergiy Sukhopara; Valerii Skryshevskyi (Біологічні студії)
Background. The nanopowder of titanium dioxide (ТіО2) is among the most demanded industrial nanomaterials; thus, it is widely used in the food industry, medicine, cosmetics production, and agriculture. It creates preconditions for constant, daily input of these particles into the organism. ТіО2 nanoparticles are known to impact the functioning of the vascular endothelium cells, changing their response to acetylcholine. However, there is almost no information about possible effects of this nanomaterial on the processes of inducing the contractile function of the vessels, using epinephrine and the activation of voltage-gated Са2+-channels. Another interesting issue is the study of polymorph-dependent effects of ТіО2 nanoparticles (NPs). This study was aimed at investigating the effect of ultradisperse ТіО2 nanoparticles of crystalline forms of anatase and rutile on the contractions of smooth muscle preparations of rat aorta, induced by the depolarization of the plasma membranes of myocytes and epinephrine-activated contractions. Materials and Methods. The commercial preparations of TiO2 nanoparticles (PlasmaChem GmbH, D-12489 Berlin, Germany) in the form of nanopowder with the average size of particles of 1–3 nm (crystalline form of rutile) and 4–8 nm (crystalline form of anatase) were used in the study. The determination of the average hydrodynamic diameter of ТіО2 nanoparticles in the suspension involved the method of dynamic light scattering. The tenzometric experiments were conducted in the isometric and isotonic registration modes using the rings of rat thoracic aorta with preserved endothelium. The contractions of aortic isolated preparations were induced by the application of a high-potassium solution (80 mM), the activator of L-type voltage-gated Са2+-channels Bay K8644, and a non-selective agonist of adrenoreceptors, epinephrine. The contractions were analysed by the methods of mechanokinetic analysis with the estimation of maximal velocities of the contraction and relaxation phases. Results. It was determined that both polymorphs of ТіО2 (at the fixed concentration of 10-4 mg/mL and 30 min pre-incubation) equally (approximately by one-third) activated the isometric and isotonic contractile responses of the aortic isolated preparations to the application of the high-potassium solution (80 mM) and the activator of Са2+-channels Bay K8644 (5 μM). In all cases, the parameters of the normalized maximal velocities of the phases of contraction and relaxation (VnC and VnR) remained at the control level. It was also found that under similar conditions of application, both types of ТіО2 NPs equally (more than twice as compared to the control) inhibited the amplitude of epinephrine-induced (1 μM) contractions of the aortic preparations. Conclusions. Ultradisperse ТіО2 NPs in a polymorph-independent manner enhance aortic contractions in the case of potential-dependent input of Са2+ ions. These nanoparticles also induce the inhibition of catecholaminergic contractions of aortic smooth muscles, which may occur due to the chelating of catecholamines by ТіО2.